Pengaruh Pemanfaatan Fitur Jaklapor JAKI Terhadap Kualitas Layanan Publik dan Kepuasan Masyarakat: Peran Kepercayaan sebagai Variabel Intervening - Firman Aulia Mulyawan; Henry Eryanto; Bayu Suhendry (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine how the JAKI app's JakLapor feature and Public Service Quality influence public satisfaction, with Trust serving as a mediating variable for users in East Jakarta. A quantitative method was employed, involving a survey of 255 participants selected via purposive sampling. Data were collected through an online questionnaire using a six-point Likert scale, and analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings indicate that the model possesses strong explanatory power, with R² values ​​of 0.881 for Trust and 0.955 for Public Satisfaction, alongside high predictive capacity (Q² Predict values ​​of 0.879 and 0.917, respectively). Effect size (f²) values ​​reveal that the impact of the JakLapor feature on Trust is small (0.053), whereas Public Service Quality makes a substantial contribution to Trust (0.497). The influence of the JakLapor feature on Public Satisfaction is very small (0.010), the impact of Public Service Quality on Public Satisfaction is moderate (0.244), and the contribution of Trust to Public Satisfaction is substantial (0.802). Hypothesis testing results indicate that the JakLapor feature has a positive and significant impact on Trust (t = 2.865); Public Service Quality has a positive and significant impact on both Trust (t = 8.254) and Public Satisfaction (t = 3.973); and Trust has a positive and significant impact on Public Satisfaction (t = 6.379). Conversely, the JakLapor feature does not have a significant impact on public satisfaction (t = 1.298). Furthermore, trust was found to act as a positive and significant link between the influence of the JakLapor JAKI feature (t = 2.178) and public service quality (t = 7.747) on public satisfaction. The findings indicate that public satisfaction with the JakLapor JAKI feature is driven more by public service quality and public trust than by the direct attributes of the application feature itself.